Overview of in situ gelling injectable hydrogels for diabetic wounds. Issue 4 (12th January 2021) - Mude, Lavanya; Sanapalli, Bharat Kumar Reddy; V, Anoop Narayanan; Singh, Sachin Kumar; Karri, Veera Venkata Satyanarayana Reddy
Abstract: Diabetes mellitus (DM) is an endocrine disorder that causes increased blood glucose than usual due to insulin impairment. In DM, several complications arise in which diabetic wound (DW) is the most devastating complication. About 25% of patients with DM expected to develop DWs in their lifetime and undergo limb amputations. Even though several treatments such as surgery, debridement, wound dressings, advanced therapies were available, the overall conclusion has been that with very few exceptions, patients still suffer from limitations like pain, frequent dress changing, high rates of failure, and cost involvement. Further, the treatments involving the delivery of therapeutic agents in treating DWs have limited success due to abnormal levels of proteases in the DW environment. In this backdrop, in situ gelling injectable hydrogels have gained special attention due to their easy encapsulation of therapeutic medications and prolonged release, filling the wound defect areas, ease of handling, and minimally invasive surgical procedures. Though the in situ gelling injectable hydrogels are developed a couple of decades ago, their use for treating DW has not yet been explored thoroughly. Thus, in this review, we have covered the sequential events of DW healing, pathophysiology, current treatments, and its limitations, along with a particular emphasis on the mechanism of action of these in situ gelling injectable hydrogels treating DWs.